ANTIOXIDANT ACTIVITIES OF LEAVES AND STEMS EXTRACTS OF WATER SPINACH (IPOMOEA REPTANS POIR) USING 2,2-DIPHENYL-1-PICRYLHYDRAZYL (DPPH), FERRIC REDUCING ANTIOXIDANT POWER (FRAP), AND CUPRIC ION REDUCING ANTIOXIDANT CAPACITY (CUPRAC) - Yohana Chayana, Grace
Antioxidant is compound that can scavenge the free radicals effect. In human cell, many free radicals can occur some diseases such as cancer. The plant which contain flavonoid can be the source of antioxidant, such as water spinach (Ipomoea reptans Poir). The objectives of this research were to study the antioxidant activities of leaves and stems extracts of water spinach using DPPH, FRAP, and CUPRAC methods; determine total phenolic content (TPC) dan total flavonoid content (TFC); analyze the correlation between TPC, TFC and AAI DPPH, FRAP, and CUPRAC; and also correlation between three methods in sample extracts. Extraction was performed by reflux method using n-hexane, ethyl acetate, and ethanol. Determination of AAI DPPH, FRAP, CUPRAC, TPC and TFC using UV-vis spectrophotometry. Correlation of TPC and TFC with AAI DPPH, FRAP and CUPRAC, and the correlation between 3 methods using Pearson’s correlation. The ethanol leaves extract gave the highest TPC (6.53 ± 0.06 g GAE/100 g), and n-hexane leaves extract showed the highest TFC (16.10 ± 0.32 g QE/100 g). AAI DPPH in the range of 1.41-25.37, FRAP 1.84 -13.40, and CUPRAC 0.78-1.71. TPC presented positive and significant correlation with AAI FRAP and CUPRAC. AAI FRAP and CUPRAC gave positive and significant correlation. In general, leaves and stems extracts had strong to very strong antioxidant activities by DPPH method. TPC leaves and stems extracts contributed to antioxidant activities by FRAP and CUPRAC methods. FRAP and CUPRAC methods gave linear result in antioxidant activities of leaves and stems extracts of water spinach.